2019
DOI: 10.4236/jsbs.2019.92002
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Consolidated Anaerobic Digester and Microbial Fuel Cell to Produce Biomethane and Electricity from Cellulosic Biomass Using Bovine Rumen Microorganisms

Abstract: Microbial fuel cells (MFCs) are bioelectrochemical systems that convert chemical energy contained in organic matter into electrical energy by using the catalytic (metabolic) activity of living microorganisms. Mediator-less two chamber H-type MFCs were constructed in the current study, using dairy digester microbial population as anode inocula to convert finely ground pine tree (Avicel) at 2% (w/v) to electricity. MFCs were placed at 37˚C and after the circuit voltage was stabilized on d9, bovine rumen microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…[48] Thus, mixed cultures with a rumen inoculum were used in cellulose-fed MFCs, as both cellulose degrading and electron transferring agents at the same time. [33,38,41,43,46,47] The highest MPD value was 0.1070 mW cm À 2 , obtained using a mixed culture with a pre-acclimated inoculum in a singlechamber IC-fed MFC. [39] To improve power production, enzymes were used to increase the hydrolysis rate of cellulose.…”
Section: Cellulose-fed Mfcsmentioning
confidence: 95%
See 1 more Smart Citation
“…[48] Thus, mixed cultures with a rumen inoculum were used in cellulose-fed MFCs, as both cellulose degrading and electron transferring agents at the same time. [33,38,41,43,46,47] The highest MPD value was 0.1070 mW cm À 2 , obtained using a mixed culture with a pre-acclimated inoculum in a singlechamber IC-fed MFC. [39] To improve power production, enzymes were used to increase the hydrolysis rate of cellulose.…”
Section: Cellulose-fed Mfcsmentioning
confidence: 95%
“…The characteristics, operating conditions, and performance, in term of MPD, of some cellulose-fed MFCs are reported in Table 2. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Insoluble cellulose (IC), with few exceptions, [34,35,44] was used as the substrate. The most part of studies on cellulose-fed MFCs were carried out using the twochamber configuration.…”
Section: Cellulose-fed Mfcsmentioning
confidence: 99%
“…We have found that the archaeal community showed a higher presence of Euryarchaeota at the phylum level, and at the genus level, Methanosaeta and Candidatus Methanoregula were abundant, followed by Methanobacterium (Zhu et al 2016). Hence, within MFCs, electricigens and methanogenic bacteria compete with each other for labile organic substrates, as well as proton transfer (Chung et al 2019;Xu et al 2021a, b). Higher power densities in each treatment group represent a higher activity of electricigens, more degradation of organic substrates and more efficient transfer of protons.…”
Section: Relationship Between Electrical Generation and Methane Produ...mentioning
confidence: 99%
“…Bioprospecting for EAB has been an important motivation for microbial research in MFCs. The search for new sources of EAB has included sludge from wastewater plants [ 6 , 7 ], sediments [ 8 , 9 ], rice paddy fields [ 10 ], forest soils [ 9 , 11 ], and rumen fluids [ 12 , 13 , 14 , 15 , 16 ]. Extreme environments have also been tested, taking inocula from salt marshes [ 17 ], saline microbial mats [ 9 ], salt lakes [ 18 ], tropical mangrove sediments [ 19 ], and acid mine drainage affected sites [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous MFC articles have reported on the use of rumen material as an inoculum. Rismani-Yazdi et al [ 14 ] and Chung et al [ 13 ] used H-type MFC reactors to demonstrate that rumen microorganisms can hydrolyze cellulose and produce electric energy.…”
Section: Introductionmentioning
confidence: 99%